Profound duodenogastric reflux causes pancreatic growth in rats. Issue 1 (January 1995) - Gasslander, T; Mukaida, H; Herrington, M K; Hinder, R A; Adrian, T E
Abstract : Although duodenogastric reflux is a physiological event, excessive reflux may be a pathogenetic factor in several diseases of the foregut, including cancer. Long term profound duodenogastric reflux produces pancreatic and gastric tumours in rats. The trophic effect of surgically induced duodenogastric reflux on the pancreas was investigated and the mechanisms involved were examined. Rats with profound reflux from a split gastroenterostomy were compared with sham operated and unoperated controls after two and six weeks. In the six week experiment, one reflux and one sham group were given the cholecystokinin (CCK) receptor antagonist devazepide (25 nmol/kg/h). Duodenogastric reflux caused a significant increase in pancreatic weight, DNA, and plasma CCK and gastrin concentrations at both two and six weeks. Devazepide substantially reduced the pancreatic weight increase after six weeks but did not abolish it completely. CCK and gastrin were not affected by devazepide. These results suggest that CCK is largely responsible for the pancreatic growth induced by reflux but another factor may also be involved. The trophic effect of duodenogastric reflux may contribute to the increased incidence of pancreatic cancer reported after gastric surgery.